Effects of Maternal Dexamethasone Exposure During Lactation on Metabolic Imbalance and Oxidative Stress in the Liver of Male Offsprings of Wistar Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: It has been reported in human and animal studies that early exposure to glucocorticoids could retard growth and subsequent development of cardio metabolic diseases. Chronic exposure to glucocorticoids induced oxidative stress. Therefore, the role of oxidative stress in some of the observed metabolic imbalance needs to be elucidated. This study examined the effects of lactational dexamethasone exposure on metabolic imbalance and oxidative stress marker in the liver of male offspring of exposed mother. Twenty lactating dams were divided into 4 groups of 5 animals each. Group 1 was administered 0.02 ml/100gbwt/day normal saline through lactation days 1-21. Group 2, 3, and 4 were administered 100 μg/kgbwt/day dexamethasone for lactation days 1-7, 1-14, and 1-21 respectively. The male offspring were thereafter separated and sacrificed at 12weeks of age for evaluation of lipid profile and oxidative stress marker in the liver.Results from this study indicate that Total Cholesterol (TC), Triglycerides (TAG) and LDL- cholesterol (LDL-C) were significantly (p
Keywords: Dexamethasone; Lactation; Oxidative Stress; Liver; offspring